Atomistic insights into formation mechanism of impact-induced augite glass from Chang'e-5 lunar regolith - Hongmei Yang; Xiaoju Lin; Xiao Wu; Haiyang Xian; Jianxi Zhu; Shan Li; Jiaxin Xi; Yiping Yang; Hongping He (Icarus, 2026)

3DED as a robust technique for decoding phyllosilicate frameworks - Yuhuan Yuan; Yiping Yang; Jiaxin Xi; Ke Wen; Haiyang Xian; Jianxi Zhu; Hongping He; Huifang Xu (Applied Clay Science, 2026)

Discovery of phage lysin against Vibrio parahaemolyticus and characterization of its antibacterial activity - Rui Zhang; Jiajun He; Fangfang Yao; Fangyuan Chen; Hongping Wei; Shengfu Huang; Yuhong Li (International Journal of Food Microbiology, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

A new mechanism for magnetite formation in loess - Yifan Hua; Guiping Ren; Hua Li; Qijun Wang; John A. Tarduno; Junfeng Huang; Chengying Liu; Yiping Yang; Ronghua Wang; Xueqin Yang; Xiaohua Han; Yongxin Pan; et al. (Science Bulletin, 2026)

Carbon mitigation potential afforded by gridded driving forces in China - Mengqi Fan; Jian Sun; Zezhuang Liu; Yilu Gu; Shengping Li; Hongping He; Xin Liu; Xiaochen Chen; Nan Wei; Xiaofeng Gao (Journal of Environmental Sciences, 2026)

Hemodynamic Evaluation for Mitral Valve Replacement - Xinyi He; Shuyi Feng; Xingchao Zhang; Fan Wu; Hongping Wang; Shizhao Wang (Annals of Biomedical Engineering, 2026)

A multiomics analysis of antioxidant and neurotransmitter disorder in honey bees caused by the bioinsecticide, Spinosad - Yinglong Yu; Zhaonan Zhang; Wencai Zhou; Dan Yao; Hongping Zhan; Xingjiang He; Ying Li; Wei Wan; Huajun Li; Xiaoping Wei (Pesticide Biochemistry and Physiology, 2026)

Mineral assemblages with smectites in simulated basalt alteration: implications for Martian aqueous environments - Tianqi Zhang; Qi Tao; Jinming Bao; Xinman Xu; Xiaorong Qin; Xiaoliang Liang; Hongping He (Applied Clay Science, 2026)

Molten NaOH-KOH assisted thermo-chemical detoxification of waste salt containing hazardous organics - Hongping He; Yong Cheng; Linhua Jiang; Youcai Zhao; Dongjie Niu; Xunchang Fei; Rong Zhang; Shijin Dai (Process Safety and Environmental Protection, 2026)

Cerium speciation and anomaly formation in mature regolith: implications for ion-adsorption type REE deposit prospecting - Mei Lu; Wei Tan; Jing Liu; Xiaoliang Liang; Stefanie M. Brueckner; Shoushu Wei; Yiping Yang; Hanliang Liu; Hongping He (Geochimica et Cosmochimica Acta, 2026)

1H NMR guided isolation of flavans from Broussonetia papyrifera and their α-glucosidase inhibitory activity - Tingting Guo; Kepu Huang; Qingfang Wang; Chen Peng; Xingping Zhang; Congxi Gao; Kou Wang; Hongping He; Mingming Li (Phytochemistry, 2026)

Enrichment and hydrothermal remobilization of HREE in the Dabu muscovite granites, South China: Insights from the REE-bearing minerals - Heng Wang; Wubin Yang; Zhiwei Bao; Hongping He; Wei Tan; Xiaoliang Liang; Jianxi Zhu (Lithos, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Source-specific quantification of microplastic-derived dissolved organic matter in sludge liquor using δ13C-labeled sludge and isotopic fingerprinting under varying conditioning treatments - Zeshan Arshad; Rabia Zafar; Min-Seob Kim; Yun Kyung Lee; Hongping He; Jin Hur (Water Research, 2026)

Bioinsecticide matrine causes a cliff-like decline and disorder of gut microbiota, transcriptomics, and metabolomics profiles in honey bees (Apis cerana) - Yinglong Yu; Zhaonan Zhang; Yuanchan Fan; Wencai Zhou; Dan Yao; Hongping Zhan; Xingjiang He; Ying Li; Wei Wan; Xiaoping Wei (Pesticide Biochemistry and Physiology, 2026)

Revealing the reaction pathways of reactive oxygen species anaerobic generation at pyrite-water interface using the ReaxFF force field - Zhaolu He; Haiyang Xian; Jianxi Zhu; Xiaoliang Liang; Hongping He (Geochimica et Cosmochimica Acta, 2026)

Five undescribed 1,3-diphenylpropanes from the leaves of Broussonetia papyrifera - Tingting Guo; Qingfang Wang; Chen Peng; Xingli Zhang; Kepu Huang; Kou Wang; Hongping He; Mingming Li (Phytochemistry Letters, 2025)

Reply to Comment on “Effect of Transcatheter Edge-to-Edge Repair on Left Ventricular Flow Features” - Xinyi He; Shuyi Feng; Fan Wu; Hongping Wang; Shizhao Wang; Xiangbin Pan (Cardiovascular Engineering and Technology, 2025)

Evaluation of the particle characteristics of aggregates from construction spoils treatment through a real-time detection multimodal module based on 3D point cloud technology - Xiaohui Sun; Bowen Liao; Shuhua Huang; Minghui Liu; Silin Wu; Xiangsheng Chen; Hongping He; Hao Xiong; Zijun Dong (Waste Management, 2025)

Aralianudasides C-E: three undescribed triterpenoid saponins from the buds of Aralia elata and its airway inflammation inhibitory activity - Juan Wang; Zhixiao Yang; Shuangya Xu; Yuhuai Long; Yuan Yuan; Yufan Chen; Die Zhang; Bang Chen; Hongping He; Baojing Li (Natural Product Research, 2025)

Biopolymer stabilization/solidification of residual waste materials for sustainable reuse in construction - Zhanbo Cheng; Ziwen Yuan; Zhibo Zhang; Hongping He; Qianhong She; Grzegorz Lisak; Xunchang Fei (Journal of Cleaner Production, 2025)

Co-adsorption of phosphate and rare earth elements (REEs) on goethite induce middle REE-enriched fractionation - Xiaoju Lin; Wenbin Yu; Xiaoliang Liang; Yoshio Takahashi; Jingwen Zhou; Yiping Yang; Meng Chen; Jianxi Zhu; Runliang Zhu; Hongping He (Geochimica et Cosmochimica Acta, 2025)

Highly oxidized exogenous materials in Chang’e 6 sample returned from the lunar farside South Pole-Aitken basin - Haiyang Xian; Shan Li; Yiping Yang; Jianxi Zhu; Xiaoju Lin; Jiaxin Xi; Wenlin Yang; Yao Xiao; Yonghua Cao; Chenyi Zhao; Miaomiao Zhang; Le Zhang; et al. (Earth and Planetary Science Letters, 2025)

Impact-induced fayalite glass from Chang'e-5 regolith revealed by electron pair distribution function and ReaxFF molecular dynamics - Hongmei Yang; Haiyang Xian; Jianxi Zhu; Xiao Wu; Shan Li; Xiaoju Lin; Jiaxin Xi; Yiping Yang; Hongping He (Icarus, 2025)

Effect of Transcatheter Edge-to-Edge Repair on Left Ventricular Flow Features - Xinyi He; Shuyi Feng; Fan Wu; Hongping Wang; Shizhao Wang; Xiangbin Pan (Cardiovascular Engineering and Technology, 2025)

Growth mechanism of long-period biotite polytypes in the Long Valley magmatic system: A non-equilibrium crystallization model - Jiaxin Xi; Yiping Yang; Huifang Xu; Aiqing Chen; Yuhuan Yuan; Wei Tan; Jianxi Zhu; Hongping He (Applied Clay Science, 2025)

Chloride corrosion destabilizes chelation of fresh and aged MSWI fly ash: Mechanism and long-term behavior - Jinyuan Lin; Lei Du; Deli Wu; Bo Yang; Xunchang Fei; Hongping He (Journal of Hazardous Materials, 2025)

Hydrothermally-targeted synthesis of Al-substituted tobermorite using MSWI fly ash with industrial SiO2 for potentially high-quality utilization - Xinlong Chen; Deli Wu; Bo Yang; Xiaofeng Gao; Xunchang Fei; Hongping He (Waste Management, 2025)

Abnormally heavy cerium stable isotope composition in regolith: Implications for redox tracing - Yuanyuan Wang; Wenshuai Li; Ryoichi Nakada; Makoto Nagasawa; Jianxi Zhu; Hongping He; Yoshio Takahashi (Geochimica et Cosmochimica Acta, 2025)

Microbial-mediated bastnaesite dissolution as a viable source of clay-adsorbed rare earth elements in the regolith-hosted deposits - Yilin He; Lingya Ma; Xurui Li; Xun Liu; Xiaoliang Liang; Jianxi Zhu; Hongping He (Geochimica et Cosmochimica Acta, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Identification of shale lithofacies by well logs based on clustering algorithms - Kun Meng; Shanbin He; Hongping Bao; Xiankun Meng; Taiping Zhao; Binfeng Cao; Xiaorong Luo; Lukman Johnson; Hongyan Yu (Acta Geophysica, 2025)

Coupled effects of iron (hydr)oxides and clay minerals on the heterogeneous oxidation of aqueous Mn(II) and crystallization of manganese (hydr)oxides - Yixuan Yang; Qingze Chen; Jing Liu; Jieqi Xing; Yiping Yang; Runliang Zhu; Hongping He; Michael F. Hochella Jr. (Geochimica et Cosmochimica Acta, 2025)

Lysine 98 in NAC20/NAC26 transcription factors: a key regulator of starch and protein synthesis in rice endosperm - Shanbin Xu; Yu Zhang; Hongping Cai; Yuzhe He; Laibao Chen; Guiping Zhang; Rongbo Chen; Chuanwei Gu; Xuan Teng; Erchao Duan; Ling Jiang; Yulong Ren; et al. (Plant Science, 2024)

Efficient concentration of viral nucleic acid in wastewater through surfactant releasing and a two-step magnetic bead extraction and purification - Ping He; Wenhao Zhou; Mengwei Jiang; Junping Yu; Hongping Wei (Science of The Total Environment, 2024)

Recovery of rare earth elements from ion-adsorption deposits using electro kinetic technology: A comparative study on leaching agents - Yongjin Xu; Gaofeng Wang; Jie Xu; Shichang Kang; Jianxi Zhu; Xiaoliang Liang; Yongqiang Yang; Jingming Wei; Hongping He (Chemical Engineering Journal, 2024)

Carbon sequestration from emerging organic contaminants: Polymerization and stabilization of secondary amine-containing fluoroquinolones associated with complexed Fe(Ⅲ) - Xiaomeng Zhang; Hongping He; Yang Zong; Zhendong Lei; Wen Liu; Deli Wu (Chemical Engineering Journal, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Indigenous microbial influence on REE enrichment and fractionation in South China weathering crusts: Insights from experimental simulations - Xurui Li; Lingya Ma; Yilin He; Xiaoliang Liang; Jianxi Zhu; Hongping He (Chemical Geology, 2024)

Resistant rare earth phosphates as possible sources of environmental dissolved rare earth elements: Insights from experimental bio-weathering of xenotime and monazite - Yilin He; Lingya Ma; Xiaoliang Liang; Xurui Li; Jianxi Zhu; Hongping He (Chemical Geology, 2024)

Study of the catalytic pyrolysis mechanism of guaiacol over seaweed-derived carbon catalyst: Based on density function theory and machine learning - Ding Jiang; Xuping Yang; Arman Amani Babadi; Xiaoxue Cheng; Qifan Ling; Hongping Li; Sirong He; Bin Cao; Xun Hu; Shuang Wang (Fuel, 2024)

Transport dynamics of rare earth elements in weathering crust soils - Shichang Kang; Bowen Ling; Gaofeng Wang; Yongjin Xu; Jie Xu; Xiaoliang Liang; Jingming Wei; Wei Tan; Lingya Ma; Jianxi Zhu; Hongping He (Science of The Total Environment, 2024)

Chemical constituents isolated from Hosta ensata and their anti-inflammatory activities - Hongping Chen; Li Yang; Weihong Zhong; Kexin Wang; Guoyue Zhong; Junwei He (Natural Product Research, 2024)

Experimental transformation of nontronite to kaolinite: implication for ferrallitization of Fe/Mg-rich clays in compositional stratigraphy on Mars - Xiaorong Qin; Jiacheng Liu; Wei Tan; Hongping He; Joseph Michalski; Yu Sun; Shangying Li; Binlong Ye; Yiping Yang; Yiliang Li (Icarus, 2024)

Surface reconstruction of ZSM-5 for in situ supporting cobalt tungstate catalysts toward oxidative desulfurization - Lingchao Xu; Junfeng She; Lixian Xu; Linhua Zhu; Jing He; Hongping Li; Huaming Li; Wei Jiang (Fuel, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Microscopic insights into acid corrosion effects on chelated MSW incineration fly ash: Mechanisms of chelate destabilization - Jinyuan Lin; Xiaofeng Gao; Deli Wu; Bo Yang; Hongping He; Xunchang Fei (Journal of Cleaner Production, 2024)

Characteristics analysis of solid waste generation and carbon emission of beer production in China - Mengqi Fan; Tao Zhou; Ziye Zhao; Yuting Du; Siyan Liu; Zihan Bi; Jiaqi Lu; Hongping He; Lei Li; Xuya Peng; Xiaofeng Gao; Yilu Gu (Environmental Research, 2024)

MOF-derived amorphous molybdenum trioxide anchored on nitrogen-doped porous carbon by facile in situ annealing for efficient oxidative desulfurization - Xin An; Xiang Gao; Jie Yin; Lixian Xu; Beibei Zhang; Jing He; Hongping Li; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2024)

Design a dual-response two-photon fluorescent probe for simultaneous imaging of mitochondrial viscosity and peroxynitrite in a thrombosis model - Miantai Ye; Xiaohui yu; Yan Yuan; Meng He; Junli zhuang; Sizheng Xiong; Jie Li; Yanying Wang; Chunya Li; Xiaoxing Xiong; Hongping Deng (Analytica Chimica Acta, 2024)

Accumulation, translocation, and fractionation of rare earth elements (REEs) in fern species of hyperaccumulators and non-hyperaccumulators growing in urban areas - Yuanyuan Wang; Liuqing He; Shiyong Dong; Haoyang Fu; Gaofeng Wang; Xiaoliang Liang; Wei Tan; Hongping He; Runliang Zhu; Jianxi Zhu (Science of The Total Environment, 2023)

Kinetics, stoichiometry, and mechanism of arsenopyrite-water interaction under anoxic conditions - Pei Chang; Xiangyu Zhu; Haiyang Xian; Jianxi Zhu; Hongping He; H. Henry Teng (Geochimica et Cosmochimica Acta, 2023)

Surface-induced oxidation of Mn(II) and crystallization of manganese (hydr)oxides on clay minerals - Yixuan Yang; Jing Liu; Runliang Zhu; Qingze Chen; Hongyan Wei; Meng Chen; Haiyang Xian; Hongping He (Geochimica et Cosmochimica Acta, 2023)

One-step solvent-free approach to constructing microporous BCNO to enhance adsorptive desulfurization - Yuan Zhang; Hongshun Ran; Xinyu Liu; Xinmiao Zhang; Tianxiao Zhu; Jie Yin; Jinrui Zhang; Linhua Zhu; Jing He; Hongping Li; Huaming Li (Chemical Engineering Journal, 2023)

Mouse phenome database: curated data repository with interactive multi-population and multi-trait analyses - Molly A. Bogue; Robyn L. Ball; David O. Walton; Matthew H. Dunn; Georgi Kolishovski; Alexander Berger; Anna Lamoureux; Stephen C. Grubb; Matthew Gerring; Matthew Kim; Hongping Liang; Jake Emerson; et al. (Mammalian Genome, 2023)
The Mouse Phenome Database continues to serve as a curated repository and analysis suite for measured attributes of members of diverse mouse populations. The repository includes annotation to community standard ontologies and guidelines, a database of allelic states for 657 mouse strains, a collection of protocols, and analysis tools for flexible, interactive, user directed analyses that increasingly integrates data across traits and populations. The database has grown from its initial focus on a standard set of inbred strains to include heterogeneous mouse populations such as the Diversity Outbred and mapping crosses and well as Collaborative Cross, Hybrid Mouse Diversity Panel, and recombinant inbred strains. Most recently the system has expanded to include data from the International Mouse Phenotyping Consortium. Collectively these data are accessible by API and provided with an interactive tool suite that enables users’ persistent selection, storage, and operation on collections of measures. The tool suite allows basic analyses, advanced functions with dynamic visualization including multi-population meta-analysis, multivariate outlier detection, trait pattern matching, correlation analyses and other functions. The data resources and analysis suite provide users a flexible environment in which to explore the basis of phenotypic variation in health and disease across the lifespan.

Investigating cooperation between competitive manufacturers under the energy performance contracting mechanism - Wenjie Zhang; Lingling He; Jing Liu; Hongping Yuan (Environment, Development and Sustainability, 2023)

Environmental effects on ammonium adsorption onto clay minerals: Experimental constraints and applications - Amber Jie Yu; Xiaoju Lin; Jianxi Zhu; Hongping He; Long Li (Applied Clay Science, 2023)

Molecular insight into DOM fate using EEM-PARAFAC and FT-ICR MS and concomitant heavy metal behaviors in biologically treated landfill leachate during coagulation: Al speciation dependence - Libing Liu; Lei Du; Sen Lu; Bo Yang; Xu Zhao; Deli Wu; Xunchang Fei; Hongping He; Dongsheng Wang (Journal of Hazardous Materials, 2023)

Combining hybrid nanoflowers with hybridization chain reaction for highly sensitive detection of SARS-CoV-2 nucleocapsid protein - Wen Yin; Ji Hu; Fang Chen; Li Zhu; Yingxin Ma; Nuo Wang; Hongping Wei; Hang Yang; Shan-Ho Chou; Jin He (Analytica Chimica Acta, 2023)

UiO-66(Zr)-based porous ionic liquids for highly efficient extraction coupled catalytic oxidative desulfurization - Jie Yin; Wendi Fu; Jinrui Zhang; Xinyu Liu; Xinmiao Zhang; Chao Wang; Jing He; Wei Jiang; Hongping Li; Huaming Li (Chemical Engineering Journal, 2023)

Differentiated subsidy mechanism for promoting construction and demolition waste recycling - Hongping Yuan; Lingling He; Huanyu Wu; Jian Zuo (Journal of Cleaner Production, 2023)

Hydrothermal alteration and the remobilization of rare earth elements during reprecipitation of nano-scale apatite in phosphorites - Jieqi Xing; Yuhang Jiang; Haiyang Xian; Wubin Yang; Yiping Yang; Wei Tan; Hecai Niu; Hongping He; Jianxi Zhu (Lithos, 2023)

Masses and size distributions of mechanically fragmented microplastics from LDPE and EPS under simulated landfill conditions - Xuhong Lu; Hongping He; Yao Wang; Yuliang Guo; Xunchang Fei (Journal of Hazardous Materials, 2023)

Effects of different soil moisture on the growth, quality, and root rot disease of organic Panax notoginseng cultivated under pine forests - Kuan Yang; Huiling Wang; Lifen Luo; Shusheng Zhu; Hongping Huang; Zhaoxia Wei; Youyong Zhu; Liwei Guo; Xiahong He (Journal of Environmental Management, 2023)

Mobilization and fractionation of rare earth elements during experimental bio-weathering of granites - Yilin He; Lingya Ma; Xurui Li; Heng Wang; Xiaoliang Liang; Jianxi Zhu; Hongping He (Geochimica et Cosmochimica Acta, 2023)

The distribution, behavior, and release of macro- and micro-size plastic wastes in solid waste disposal sites - Xunchang Fei; Hongping He; Xiaoqing Pi; Xuhong Lu; Qinqin Chen; Jun Ma; Yao Wang; Mingliang Fang; Chuangzhou Wu; Shijin Feng (Critical Reviews in Environmental Science and Technology, 2023)

Nanoscale chemomechanical variations of montmorillonite induced by the specificity of counterions—An in situ XRD and AFM study - Yingya Wang; Lingyu Ran; Lingya Ma; Runliang Zhu; Jingming Wei; Hongmei Liu; Yunfei Xi; Jianxi Zhu; Hongping He (Applied Clay Science, 2023)

Highly-efficient molten NaOH-KOH for organochlorine destruction: Performance and mechanism - Shijin Dai; Libing Liu; Hongping He; Bo Yang; Deli Wu; Youcai Zhao; Dongjie Niu (Environmental Research, 2023)

Zircon texture and composition fingerprint HREE enrichment in muscovite granite bedrock of the Dabu ion-adsorption REE deposit, South China - Heng Wang; Hongping He; Wubin Yang; Zhiwei Bao; Xiaoliang Liang; Jianxi Zhu; Lingya Ma; Yufeng Huang (Chemical Geology, 2023)

A luciferase based automated assay for rapid and sensitive detection of SARS-CoV-2 antibodies - Wenhao Zhou; Ping He; Huan Liu; Hongping Wei; Junping Yu (Analytica Chimica Acta, 2023)

Taberdines L and M, two new alkaloids from Tabernaemontana divaricata - Lingling Han; Kepu Huang; Chen Chen; Wentao Zhu; Yehan Ma; Xiaojiang Hao; Hongping He; Yu Zhang (Natural Product Research, 2022)

Superimposed microstructures of pyrite in auriferous quartz veins as fingerprints of episodic fluid infiltration in the Wulong Lode gold deposit, NE China - Wei Tan; Steven M. Reddy; Denis Fougerouse; Christina Yan Wang; Bo Wei; Haiyang Xian; Yiping Yang; Hongping He (Mineralium Deposita, 2022)

Environmental-sulfur-controlled surface properties of pyrite: a first principles PBE + U study - Haiyang Xian; Xiao Wu; Jianxi Zhu; Runxiang Du; Jingming Wei; Runliang Zhu; Hongping He (Physics and Chemistry of Minerals, 2021)

Mechanical Model and Control Technology of Roadside Gangues in Gob-Side Entry Retaining by Roof Cutting - Zhen Zhu; Manchao He; Xuchun Wang; Hongping Yuan (Geotechnical and Geological Engineering, 2020)

Two new monoterpenoid indole alkaloids from Tabernaemontana divaricata - Huansha Yuwen; Yuxi Yuan; Xiaojiang Hao; Hongping He; Yu Zhang (Natural Product Research, 2019)

Genome-wide association mapping of root system architecture traits in common wheat (Triticum aestivum L.) - Peng Liu; Yirong Jin; Jindong Liu; Caiyun Liu; Hongping Yao; Fuyi Luo; Zhihui Guo; Xianchun Xia; Zhonghu He (Euphytica, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Chemical and structural studies of coexisting 1M- and 2M1-polytypes in synthetic fluorophlogopites and influence of Al on the polytype formation - Aiqing Chen; Wei Tan; Hongping He; Guowu Li; Xinye Wu; Qi Tao; Jianxi Zhu (Physics and Chemistry of Minerals, 2019)

Photochemically Induced Electron Transfer: Simultaneously Decolorizing Dye and Reducing Cr(VI) - Minwang Laipan; Haoyang Fu; Runliang Zhu; Linda Rivera; Gangqiang Zhu; Jianxi Zhu; Hongping He (Water, Air, & Soil Pollution, 2017)

CKB1 is involved in abscisic acid and gibberellic acid signaling to regulate stress responses in Arabidopsis thaliana - Congying Yuan; Jianping Ai; Hongping Chang; Wenjun Xiao; Lu Liu; Cheng Zhang; Zhuang He; Ji Huang; Jinyan Li; Xinhong Guo (Journal of Plant Research, 2017)

Zn2+ and mPTP Mediate Endoplasmic Reticulum Stress Inhibition-Induced Cardioprotection Against Myocardial Ischemia/Reperfusion Injury - Guochen Wang; Hongping Huang; Huan Zheng; Yonggui He; Yidong Zhang; Zhelong Xu; Liu Zhang; Jinkun Xi (Biological Trace Element Research, 2016)

Chitooligosaccharide Inhibits Scar Formation and Enhances Functional Recovery in a Mouse Model of Sciatic Nerve Injury - Hongping Hou; Lihai Zhang; Zuguang Ye; Jianrong Li; Zijian Lian; Chao Chen; Rong He; Bo Peng; Qihua Xu; Guangping Zhang; Wenbiao Gan; Peifu Tang (Molecular Neurobiology, 2016)

The structure of montmorillonites modified with zwitterionic surfactants and their sorption ability - Jianxi Zhu; Yanhong Qing; Lingya Ma; Runliang Zhu; Hongping He (Mineralogy and Petrology, 2015)

The oxidation state and microstructural environment of transition metals (V, Co, and Ni) in magnetite: an XAFS study - Xiaoliang Liang; Zisen He; Wei Tan; Peng Liu; Jianxi Zhu; Jing Zhang; Hongping He (Physics and Chemistry of Minerals, 2015)

Erratum to: Autophagy Reduces Neuronal Damage and Promotes Locomotor Recovery via Inhibition of Apoptosis after Spinal Cord Injury in Rats - Peifu Tang; Hongping Hou; Licheng Zhang; Xia Lan; Zhi Mao; Daohong Liu; Chunqing He; Hailong Du; Lihai Zhang (Molecular Neurobiology, 2014)

Autophagy Reduces Neuronal Damage and Promotes Locomotor Recovery via Inhibition of Apoptosis After Spinal Cord Injury in Rats - Peifu Tang; Hongping Hou; Licheng Zhang; Xia Lan; Zhi Mao; Daohong Liu; Chunqing He; Hailong Du; Lihai Zhang (Molecular Neurobiology, 2014)

Studies on the solid acidity of heated and cation-exchanged montmorillonite using n-butylamine titration in non-aqueous system and diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy - Hongmei Liu; Dong Liu; Peng Yuan; Daoyong Tan; Jingong Cai; Hongping He; Jianxi Zhu; Zhiguang Song (Physics and Chemistry of Minerals, 2013)

Characterizing ecological risk for polycyclic aromatic hydrocarbons in water from Lake Taihu, China - Guanghui Guo; Fengchang Wu; Hongping He; Ruiqing Zhang; Chenglian Feng; Huixian Li; Ming Chang (Environmental Monitoring and Assessment, 2012)

Distribution characteristics and ecological risk assessment of PAHs in surface waters of China - GuangHui Guo; FengChang Wu; HongPing He; RuiQing Zhang; HuiXian Li; ChengLian Feng (Science China Earth Sciences, 2012)

Spiro[pyrrolidine-2,3′-oxindole] derivatives synthesized by novel regionselective 1,3-dipolar cycloadditions - Gang Chen; Jing Yang; Suo Gao; Hongping He; Shunlin Li; Yingtong Di; Ying Chang; Yang Lu; Xiaojiang Hao (Molecular Diversity, 2012)

Flavone and isoflavone derivatives of terrestrial plants as larval settlement inhibitors of the barnacle Balanus amphitrite - Xiaojian Zhou; Zhen Zhang; Ying Xu; Cuili Jin; Hongping He; Xiaojiang Hao; Pei-Yuan Qian (Biofouling, 2009)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)